Synchronizing audio and haptic feedback to read webpage - Sulaiman, S. (Institute of Electrical and Electronics Engineers Inc., 2014)
The limitations of a Website's accessibility in terms of its text attributes representation in web pages hinder the visually impaired users from having a comprehensive understanding of the web content. Current assistive technology such as screen reader and refreshable Braille device are unable to represent this non-textual attributes to the visually impaired. This paper presents a study that examines the significance of text attributes to support Web accessibility and improve understanding of the content. It was hypothesized that the synchronization of audio and haptic feedbacks could improve Web accessibility through text attributes identification; thus, providing comprehensive understanding of the webpage. The study involves development of a prototype system that synchronizes audio and haptic to read webpage and represents text attributes. A mixture of qualitative and quantitative data collection methods was adopted. Interviews with the visually impaired users were conducted to gather their requirements for the prototype. A user testing involving those who suffer from high degree of visual impairment was carried out to evaluate the prototype. B The findings show significant improvement in web browsing performance and text attributes identification using the prototype as compared to the existing screen reader. Â© 2014 IEEE.